Species Diversity of Trees with Traditional Medicinal Uses: A Core-Buffer Zone Comparison in a Biosphere Reserve - Priatna, Dolly; Denny; Monk, Kathryn A; Susilo, Adi; Hartiningtias, Diny (Institut Pertanian Bogor (IPB University), 2025)
Giam Siak Kecil-Bukit Batu, a UNESCO Biosphere Reserve, uses a zoned management approach, including core, buffer, and transition zones. The core zone prioritizes biodiversity conservation, buffer zones mitigate human impacts, and transition zones focus on sustainable development. The diversity and density of medicinal tree species in the core and buffer zones of this reserve were investigated. It was hypothesized that the core zone would support greater diversity and density of medicinal trees than the buffer zone. Standardized plot sampling was conducted using 1-ha plots, each subdivided into 25 subplots (20 m × 20 m). Trees with a diameter at breast height exceeding 10 cm were inventoried, measured, and identified, with voucher specimens collected for herbarium confirmation. A total of 52 medicinal tree species from 27 families and 36 genera were recorded. Species richness was higher in the buffer zone (39 species) than in the core zone (29 species). These findings underscore the ecological significance of buffer zones in conserving medicinal tree diversity and providing sustainable resources for local communities. The observed species richness in the buffer zone challenges the conventional assumption that core zones harbor higher biodiversity, highlighting the need for further research on sustainable resource management in buffer zones.